A Case of an Unusually Aggressive Cutaneous Anaplastic Large T-Cell Lymphoma in an HIV Patient Treated with CHOP - Jorge Hurtado-Cordovi; Louay Hanna; Vladimir Gotlieb; Alan S. Multz; Anastasia Pigal (Case Reports in Oncological Medicine)
Anaplastic large cell lymphoma (ALCL) is the second most common malignancy of T-cell phenotype. This case report describes an unusual rapidly progressing cutaneous anaplastic large T-cell lymphoma in an HIV patient. Our patient is a twenty-year-old African American male with perinatally acquired HIV who presented with a 2×2 centimeter necrotic lesion in the right 1st toe; however, 2-3 weeks later multiple smaller lesions appeared on the anterior aspect of the right foot, ankle, and thigh. Biopsy showed cells strongly positive for CD3 and CD30 and negative for CD56 and the ALK gene product. CT of the chest, abdomen, and pelvis was negative for extracutaneous involvement favoring cutaneous ALCL. Patient was treated with 6 cycles of CHOP (cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisone) chemotherapy and went into complete remission. Due to the aggressive course that this malignancy follows in HIV patients we suggest prompt treatment with systemic therapy.